2018
DOI: 10.15666/aeer/1604_45934603
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Hair Identification Key of Common Mammals in Turkey

Abstract: The aim of this study was to research the morphology and to make ready a hair identification key for common mammals in Turkey and also to make up a comprehensive method for the preparation of hair identification key for Turkey's mammals. Despite the wide application of this technique in the determination of diet composition in large carnivores, it has not been used in Turkey up to this point, thus this paper is the first study and an appropriate guide for using this technique in ecological studies and manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
3
4
0
Order By: Relevance
“…4 ). Sari and Arpacik (2018) also found similar results in the medulla and cuticular patterns of canids from Turkey. Using percentage medulla width, we were able to differentiate Himalayan wolf (having medullary width of 81.4% [SE: 0.7]) from other Canis species (70-75%), but failed to differentiate between Indian wolves and jackals (Table 2 ) .…”
Section: Discussionsupporting
confidence: 73%
“…4 ). Sari and Arpacik (2018) also found similar results in the medulla and cuticular patterns of canids from Turkey. Using percentage medulla width, we were able to differentiate Himalayan wolf (having medullary width of 81.4% [SE: 0.7]) from other Canis species (70-75%), but failed to differentiate between Indian wolves and jackals (Table 2 ) .…”
Section: Discussionsupporting
confidence: 73%
“…L.) hair (Table 1). Indeed, this hair showed a multicellular medulla with continuous pattern and structure partially filled lattice, although not well preserved [70]. These last findings were in line with the faunal remains found in many coeval archaeological sites and could have been inhaled during meat preparation (e.g., bird plucking) or derive from fragments of epidermis chewed during the meal.…”
Section: Resultssupporting
confidence: 56%
“…The authors stated that the scales are presented transversely with distant margin and irregular wave scale. Conversely Sari and Arpacik [20] found irregular rippled scale patterns can be observed in all studied species except the Bovidae family and wild boar, and cited that this structure in the entire hair length of the Bovidae family and wild boar is regularly waved.…”
Section: Discussionmentioning
confidence: 95%
“…De Marinis e Agnelli [31] mentioned that in microscopic morphology the use of medulla structure has priority over the cuticle pattern and the use of the cuticle pattern individually will cause confusion, but Sari & Arpacik [20] reported that at lower levels, such as subfamily and genus, the medulla structure does not give the correct results in species identification due to its high resemblance, so the cuticle pattern (trichological analysis) was used for identification in all species.…”
Section: Discussionmentioning
confidence: 99%